Recent Advances in Chemical Functionalisation of Graphene and Sensing Applications - Ijeomah, Geoffrey; Fahmi, Samsuri; Obite, Felix; Mohamad Adzhar, Md Zawawi (2020)
Graphene, a one-atom-thick, sp2-hybridised allotrope of carbon has attracted massive interest due to its outstanding electrical, mechanical, thermal and optical properties. The material of graphene is remarkably stable, with a huge potential for developing various types of sensors, including biomedical sensing where enhanced specificity, sensitivity, label-free nature and cost effectiveness for rapid point-of-care detection of diseases are paramount. This is due to the simplicity with which its electronic properties can be modified since each atom in the structure directly interacts with the sensing environment. These unique characteristics can be exploited for several kinds of sensing applications such as electrochemical and electrical sensors as well as optical sensors. While pristine graphene is desirable for applications that require high electrical conductivity, many other applications require functionalised graphene for optimal performance. Therefore, the functionalisation of graphene is a significant step towards tuning its structure for various sensing applications. In this review, we report recent technological progress in the chemical functionalisation of graphene and its sensing applications.